Implementasi Metode Design Thinking Dalam Perancangan UIUX Aplikasi Wisata Bali - I Kadek Agus Candra Widnyana; I Made Widiartha (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Many tourists find it difficult to efficiently plan or find tourist destinations in Bali. They need a convenient way to search for attractions or plan their trips. A system is needed to facilitate the search and planning of their tourist trips, which can be supported by utilizing technology such as smartphones and mobile applications, making UI/UX crucial to help users solve their problems. This design is carried out using Figma tools and the design thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. This research aims to analyze and implement the Design Thinking method in designing the user interface (UI/UX) of a tourist application focusing on tourist destinations in Bali.